Clinician-reported Gloucester Comfort Scale scores underestimate patient discomfort and pain during colonoscopy: insights from comparison with a patient-reported experience measure - van Bokhorst, Querijn N. E.; Geerlings, Charmayne V.; van der Vlugt, Manon; Nass, Karlijn J.; Borkent, Jos W.; Neilson, Laura J.; Fockens, Paul; Rees, Colin J.; Dekker, Evelien (Endoscopy, 2025)
Patient experience is a fundamental element of colonoscopy. The Gloucester Comfort Scale (GCS) is used by clinicians to report patient comfort. However, insights regarding the extent to which clinician-reported GCS scores represent the patient’s experience are lacking. We assessed the level of agreement between clinician-reported GCS scores and patient-reported discomfort and pain.Consecutive patients undergoing colonoscopy at two Dutch endoscopy clinics were included. Patient comfort during colonoscopy was reported using the GCS (1–5 scale). Patients’ colonoscopy experiences were assessed using the Newcastle ENDOPREM, a validated endoscopy patient-reported experience measure (PREM). Patients reported both discomfort and pain levels experienced during colonoscopy on a 1–5 scale. Levels of agreement were assessed using Cohen’s kappa statistic.For 243 included patients, the GCS score was higher than the PREM discomfort score in 52 patients (21%) and lower in 72 (30%). GCS score was higher than the PREM pain score in 39 patients (16%) and lower in 71 (29%). Moderate-to-severe discomfort and pain (scores ≥3) were reported by 53 patients (22%) for discomfort and 60 patients (25%) for pain. For these patients, the GCS underestimated discomfort and pain levels in almost all cases (discomfort 49/53 [92%], pain 54/60 [90%]). Agreement between GCS scores and PREM discomfort and pain scores were minimal (Cohen’s κ 0.34) and weak (Cohen’s κ 0.47), respectively.Clinician-reported GCS scores frequently underestimated the level of discomfort and pain reported by patients. For accurate monitoring of patients’ colonoscopy experiences, the use of PREMs should be considered.